(untitled) (Journal of Dhaka Medical College, 2015)
Objective: To evaluate the distribution of common medical conditions related to stroke among Bangladeshi patients. Methods: This is an observational study. It involved 336 stroke patients from different medicine words in Dhaka Medical College Hospital over a period of twelve months. We evaluated some common established medical conditions observed among stroke patients e.g. age, sex, family history, hypertension, diabetes, ischemic heart disease, smoking, obesity, dyslipidaemia, alcoholism, use of oral contraceptive pill, lack of fresh fruit consumption etc. A predesigned check list was used for data collection. Result: Among the 336 patients, Most of the stroke events occurred after the age of forty (82.3%) and the ischemic stroke (72%) being the most common. Other than the non modifiable risk factors (advancing age, sex, Family history of stroke) hypertension was the most common factor found in relation to stroke patients (57.6%) followed by smoking (44.6%), tobacco use (24.3%), OCP use in female (40% of female stroke), diabetes (23%), ischemic heart disease (17.1%), obesity (10.6%) and dyslipidaemia (5.3%). Conclusion: Stroke is common after the age of forty. Ischemic events are commonest type of stroke. Hypertension, smoking, diabetes, tobacco use, and ischemic heart disease were five most common conditions related to stroke. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 167-174